Delay discounting, probability discounting, and interdental cleaning frequency - Anthony DeFulio; Mark Rzeszutek (BMC, 2022)
Abstract Background Interdental cleaning is recommended by dentists but many people do not floss regularly. The health benefits of interdental cleaning are delayed, and sensitivity to delay is an important factor in many health behaviors. Thus, the present studies explore the relationship between frequency of flossing, and sensitivity to delayed and probabilistic outcomes. Method Crowd-sourced subjects were recruited in two studies (n = 584 and n = 321, respectively). In both studies, subjects reported their frequency of flossing and completed delay discounting and probability discounting tasks. Discounting was measured with area under the curve, and linear regression was used to analyze the results. Results Findings show that higher levels of delay discounting were associated with less frequent flossing (p < 0.001, both studies). In contrast, probability discounting was not significantly associated with flossing frequency (ns, both studies). Conclusion The findings are consistent with prior studies involving other health behaviors such as attendance at primary care and medication adherence. Results suggest that interventions that reduce delay discounting may help promote regular interdental cleaning, and that delay discounting is a more robust predictor of health behaviors than probability discounting. In addition, interdental cleaning appears to be a reasonable target behavior for evaluating potentially generalizable behavioral health interventions. Thus, interventions that are successful in promoting oral health behaviors should be considered as candidates for evaluation in other health behavior domains.